Practicality and Technical Communication in Corvi Housing Typologies [Practicidad y Comunicación de Lo Técnico en Las Tipologías de Vivienda Corvi] - Alvarez-Campos, D (Universidad de Chile, Instituto de la Vivienda, 2021)
In December 1972, the Sub Department of Design of the Corporación de la Vivienda (CORVI) published a document with eighteen housing prototypes developed by its teams between 1966 and 1971. This document was the result of the previous experience of those teams in developing a large part of the social housing built in Chile, of the work of systematization and standardization of that set of works, and of the design indications given by the managers of these teams. Drawing on the document itself, secondary sources that report on CORVI’s decisions, and interviews with Orlando Sepúlveda Mellado, an architect member of CORVI’s design teams, this paper analyzes the practical meaning of “Tipología de viviendas racionalizadas 1966-1972” and suggests that it performs a non-canonical mode of the notion of typology, articulates a standardization of project ideas, and responds to the contingencies of the sociomaterial environment. This helps to conclude that the inaccuracies observed in the document are part of an objectual strategy of communication of the technical aspect that aims at its practicality, that is, to efficiently narrate the complexity of architectonic rationalization as a political and socio-technical program. © 2021, Universidad de Chile, Instituto de la Vivienda. All rights reserved.